Preparation of asymmetric Janus hollow silica microparticle and its application on oily wastewaters - Hailong Zhang; Ting Qu; Hairong Wang; Weixing Wu; Fangfang Lu; Jiguang Ou; Genmin Zhu; Liangjun Gao; Longsheng Cheng (Scientific Reports, 2023)
Abstract Janus nanoparticles have aroused the interest of scholars because of their highly efficient emulsification of spilled oils in wastewater. In this work, interfacially active Janus hollow glass microparticles (J-HGMPs) of asymmetric wettability were designed and synthesized in order to achieve more efficient separation of emulsified oil droplets from oily wastewater. Surface characteristic techniques such as FTIR, SEM, zeta potential and contact angle measurements had been employed to assess the amphiphilic surface properties of J-HGMPs. The oil removal/recovery performance of J-HGMPs in different oil–water systems and their interfacial activities were studied. As a particulate emulsifier, J-HGMPs could remove/recover > 96% oil from oil–water mixed phase. The results showed that J-HGMPs had strong interfacial activities and anchored firmly at oil/water interfaces. This high adsorption energy was also evaluated and verified via the calculation of Gibbs free energy. Overall, this study provided a novel and low-cost oil recovery method via a convenient buoyancy force that could be effectively applied in the treatment of oil spills while achieving the goal of benign and green environmental protection.